Pengaruh Pemberian Hormon Naftalen Acetyl Acyd (NAA) dan Kinetin pada Kultur Jaringan Nanas Bogor (Ananas comosus (L.) Merr.) cv. Queen - Imam Mahadi (Biology Department, Faculty of Science and Technology, Univeristas Jambi, Indonesia, 2016)
Pineapple (Ananas comosus (L.) Merr.) is one tropical fruits are highly favored by the Indonesian people and the potential for export commodities. This research is aimed to determine the effect of NAA and kinetin with different concentrations of Murashige Skoog medium (MS) to mikropropagasi Bogor pineapple (Ananas comosus (L.) Merr.) cv. Queen. The research design used was completely randomized design (CRD) factorial with two factors, each factor consists of 4 degree of concentration are: NAA hormone concentrations (0-1 ppm) and kinetin (0-3 ppm) with 3 replications. Parameters observed that the percentage of explants growing, lengt of shoot ,number of shoots and number of roots. The data were analyzed further test ANAVA and DMRT at 5% level. The results showed that the percentage of explants all treatments grew 100%, lengt of shoot is 7,73 cm in control, the highest number of shoots in treatment N0,25K3 is 13.67, and the highest number of roots in the treatment N1K0 is 11.67 weeks after initiation. The results concluded that the combined treatment N0,25K3 is the best treatment for micropropagation of pineapple cv. bogor Queen.